$δ p(Λ,p)$-open Sets in Topological Spaces (European Journal of Pure and Applied Mathematics, 2023)
This paper deals with the notion of $δ p(Λ,p)$-open sets. Some properties of $δ p(Λ,p)$-open sets and $δ p(Λ,p)$-closed sets are investigated. Moreover, several characterizations of $δ p(Λ,p)$-$\mathscr{D}_1$ spaces and $δ p(Λ,p)$-$R_0$ spaces are established.
Keywords: $δ p(Λ,p)$-open set; $δ p(Λ,p)$-$\mathscr{D}_1$ space; $δ p(Λ,p)$-$R_0$ space